2023
DOI: 10.3389/fimmu.2023.1183542
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of the programmed cell death 1 signaling pathway in sepsis induced immunosuppression

Abstract: Sepsis is a multiple organ dysfunction syndrome caused by the host’s immune response to infection, with extremely high incidence and mortality. Immunosuppression is an essential pathophysiological alteration that influences the clinical treatment and prognosis of sepsis. Recent studies have suggested that the programmed cell death 1 signaling pathway is involved in the formation of immunosuppression in sepsis. In this review, we systematically present the mechanisms of immune dysregulation in sepsis and elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…According to the conventional perspective, following an initial phase of excessive inflammation, a subsequent phase of diminished inflammation, partially attributed to the release of anti-inflammatory cytokines, leads to profound immunosuppression ( Sheth et al, 2019 ). Currently, preliminary results indicated that the stages of inflammation promotion and immune suppression may occur concurrently ( Zhong and Yin, 2023 ), rendering the interaction between host and pathogen conducive for disease development. The high-risk factors for sepsis patients encompass advanced age, gender, presence of immunosuppressive diseases, medications, history of cancer, diabetes mellitus, alcohol misuse, and the utilization of indwelling urinary catheters ( Tokuda et al, 2023 ).…”
Section: Overeview Of Sepsismentioning
confidence: 99%
“…According to the conventional perspective, following an initial phase of excessive inflammation, a subsequent phase of diminished inflammation, partially attributed to the release of anti-inflammatory cytokines, leads to profound immunosuppression ( Sheth et al, 2019 ). Currently, preliminary results indicated that the stages of inflammation promotion and immune suppression may occur concurrently ( Zhong and Yin, 2023 ), rendering the interaction between host and pathogen conducive for disease development. The high-risk factors for sepsis patients encompass advanced age, gender, presence of immunosuppressive diseases, medications, history of cancer, diabetes mellitus, alcohol misuse, and the utilization of indwelling urinary catheters ( Tokuda et al, 2023 ).…”
Section: Overeview Of Sepsismentioning
confidence: 99%